2016
DOI: 10.3390/ijerph13111116
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Low Carbon Economy Efficiency with a Three-Stage Data Envelopment Analysis: A Comparison of the Largest Twenty CO2 Emitting Countries

Abstract: This paper employs a three-stage approach to estimate low carbon economy efficiency in the largest twenty CO2 emitting countries from 2000 to 2012. The approach includes the following three stages: (1) use of a data envelopment analysis (DEA) model with undesirable output to estimate the low carbon economy efficiency and calculate the input and output slacks; (2) use of a stochastic frontier approach to eliminate the impacts of external environment variables on these slacks; (3) re-estimation of the efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…This result reveals that there is no significant difference in the mean efficiencies of the two case scenarios. The results of this study to a large extent confirm the findings of Liu and Liu [59], who estimated the energy performance of the top 20 CO 2 emitting nations. Wang et al [48] also obtained similar findings, assessing the energy efficiency of 25 nations.…”
Section: Case Scenario 2: Malmquist Productivity Index (Mpi) Without supporting
confidence: 88%
See 1 more Smart Citation
“…This result reveals that there is no significant difference in the mean efficiencies of the two case scenarios. The results of this study to a large extent confirm the findings of Liu and Liu [59], who estimated the energy performance of the top 20 CO 2 emitting nations. Wang et al [48] also obtained similar findings, assessing the energy efficiency of 25 nations.…”
Section: Case Scenario 2: Malmquist Productivity Index (Mpi) Without supporting
confidence: 88%
“…Again, based on CO 2 emission concerns, Liu and Liu [59] employed the three-stage DEA methodological framework to assess the efficiency of the top 20 CO 2 emitting economies from 2000 to 2012 with the incorporation of CO 2 as a bad output. Wang et al [60] developed an integrated super SBM-DEA and Malmquist productivity index (MPI) method to study the energy efficiency estimates of 17 nations.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, DEA SBM was frequently applied to deal with the presence of undesirable outputs; for example, the study carried out by Apergis [23] used an SBM to measure the energy efficiency of selected Organisation for Economic Co-operation and Development (OECD) countries. Regarding the concern about CO 2 emissions, Liu and Liu [24] used three-stage DEA in their study to measure the low-carbon economy efficiency of the top 20 largest CO 2 emitters from 2000 to 2012 with the presence of CO 2 emissions as an unwelcome output. Lenz.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao and Zhong () evaluated the LCEE between different provinces in China by using a three‐stage DEA model with the dynamic Malmquist Productivity Index (MPI), and suggested that the development of LCE requires a transition of the current economic structure. Liu and Liu () employed a three‐stage DEA model in estimating LCEE in the 20 largest CO 2 ‐emitting countries during 2000–2012.…”
Section: Literature Reviewmentioning
confidence: 99%